Differential Effect of Dietary Fibers in Intestinal Health of Growing Pigs: Outcomes in the Gut Microbiota and Immune-Related Indexes - Luo, Yuheng; Liu, Yang; Li, Hua; Zhao, Yao; Wright, André-Denis G.; Cai, Jingyi; Tian, Gang; Mao, Xiangbing (Frontiers in Microbiology, 2022)
Although dietary fibers (DF) have been shown to improve intestinal health in pigs, it is unclear whether this improvement varies according to the type/source of DF. In the current study, we investigated the impact of dietary supplement (15%) of pea-hull fiber (PF), oat bran (OB) and their mixture (MIX, PF and OB each accounted for 7.5%) in the growth performance as well as intestinal barrier and immunity related indexes in growing pigs. Twenty-four cross-bred pigs (32.42 ± 1.95 kg) were divided into 4 groups, CON (basal diet with no additional DF), PF, OB and MIX. After 56 days of feeding, we found that the growth performance of PF pigs was decreased (P < 0.05) compared to pigs in other groups. Results of real-time PCR and Western Blot showed that the improvement of immune related indexes (e.g. IL-10) in OB and MIX pigs mainly presented in the ileum, while the improvement of intestinal barrier related indexes (e.g. MUC1 and MUC2) mainly presented in the colon. Whether in the ileum or colon, such improvement of immune function may be dependent on NOD rather than TLR associated pathways. Amplicon sequencing results showed that PF and MIX pigs shared a similar bacterial community, such as lower abundance of ileal Clostridiaceae and colonic Streptoccocus than that of CON pigs (P< 0.05). Our results indicate that OB and MIX rather than PF benefits the intestinal health in growing pigs, and multiple-sourced DF may reduce the adverse effect of single-soured DF on the growth performance and gut microbiota in pigs.